Estudo de viabiliade econômica do processo de pirólise e craqueamento termo-catalítico em escala piloto utilizando-se material ligno-celulósico, lipídico, de óleo de palma (elaeis guineensis, jacq) e resíduo da neutralização do óleo de palma - AMARAL, Anderson Rocha (Universidade Federal do Pará, 2023)
In this work, it is accomplished a tecno-economic assessment of the production of bio-oil, coke and gas, via thermos-catalytic pyrolysis followed by distillation. The raw materials were: lipid-base material (residual fat/scum from fat retention box of the University Restaurant at the Federal University of Pará - UFPA), lignin-cellulosic material Açaí seed (Euterpe oleracea. Mart), palm oil and neutrilzing sludge palm oil. From the literature is made a review of the physic-chemical analysis of the raw materials, of the bio-oil and of chemical composition of the biofuels produced (biogasoline, bioquerosene, light-diesel and heavy-diesel). Are also presented the bio-oil yields for each experiment of pyrolysis and distillation and compared with the literature. The economic indicators demonstrated feasibility of the all projects, with exception with the use of açaí seeds. The indicators used to analysis the projects were: a) simple payback criterion, b) discounted payback, c) net present value (NPV), d) internal rate of return (IRR), and e) index of profitability (IP). The minimum fuel selling price (MFSP) obtained is this work for the biofuels was of 1.34 US$/L for all projects, with exception to the palm oil, which was 1,59 US$/L. The sensibility analysis demonstrated that the pyrolysis and distillation yields are the most important variables to affect the minimum fuel selling price (MFSP).